Development of hybrid organic-inorganic coating based on carbon dots on bacterial cellulose using sol-gel route - Onishi, Bruno Seiki Domingos [UNESP]; Bortoletto-Santos, Ricardo [UNESP]; Neto, Elias Paiva Ferreira [UNESP]; Ribeiro, Sidney José Lima [UNESP] (My University, 2022)
The luminescence quenching by aggregation of carbon dots (CD) could be solved by functionalizing the surface with an alkoxysilane, bounding the nanoparticle directly in the polymer network.The reaction was monitored with ATR-FTIR and bacterial cellulose (BC) was coated with the precursor using sol-gel route, showing blue luminescence of CD.